Optimizing Agricultural Area Planning in Supporting Food Security in Asahan Regency: A Case Study Kecamatan Rawang Panca Arga - Irfan; Abdi Sugiarto (Journal of Information Technology, computer science and Electrical Engineering, 2024)
This study aims to research the Optimization of Agricultural Area Planning in Supporting Food Security in Asahan Regency: A Case Study of Rawang Panca Arga District. The qualitative research method described above provides a strong foundation to explore and understand the complexity of agricultural area planning and food security in Rawang Panca Arga District. With the right approach, this research is expected to provide in-depth insights and effective solutions to overcome the challenges faced in the agricultural sector in Asahan Regency. Research results The capacity of human resources, especially farmers, needs to be increased through training and extension programs. With better knowledge of modern agricultural techniques, farmers will be better able to optimize crop yields and maintain food security independently. Government and institutional support is very important in supporting the sustainability of agricultural area planning. Policies that support incentives for farmers, subsidies, and access to markets can encourage the sustainability and competitiveness of the agricultural sector in Rawang Panca Arga District. With the optimization of agricultural areas that are planned effectively, Rawang Panca Arga District has the potential to become one of the main pillars of food security in Asahan Regency. Increasing production and sustainability of food supply will make a real contribution to the welfare of people in this region. In conclusion, the optimization of agricultural area planning in Rawang Panca Arga District has significant potential to support food security in Asahan Regency, as long as it is carried out with comprehensive planning and continuous support from various parties.